MENTAL HEALTH AND THE LIBERTARIAN STRUCTURES OF SOCIAL MEDIA PLATFORMS: EXPERIENCES OF PEOPLE WITH EATING DISORDERS - Saukko, Paula (AoIR Selected Papers of Internet Research, 2023)
Most research on social media and mental health takes a social psychological focus on associations between types of use (social comparisons) or content (idealised images of thinness) and negative effects. Drawing on critical media studies research on platforms, this presentation shifts the conversation towards exploring how social media platforms or mechanisms shape vulnerable users’ experiences of use and content. Interviews with people with eating disorders (EDs) (n=31) highlighted three key experiences: (i) messaging apps that afforded interpersonal communication with chosen trusted audiences and modes of interaction enhanced wellness, whereas platforms and features pushing interaction and extensive, competitive connections were distressing and shunned, (ii) diet influencers, reeled by algorithms, were especially harmful for people with EDs who sought to steer their feeds towards recovery influencers, which however could rehash triggering aesthetic codes informed by the attention economy; (iii) social media support groups, coaches and mental health advice were deemed useful, however the sheer plenitude of offer and business models also created a minefield. The findings map onto historical intertwining of the countercultural quest to open a space for user-generated content and interaction and commercial entrepreneurialism, both characterised by libertarianism. The participants sought to carve out spaces in social media with trusted friends and alternative vernacular content. Yet, the platforms catapulted them out of their comfort zones into harmful interactions and content streams. The problem here is not specific use or content, but libertarian and commercial social media infrastructures that do not afford safe spaces for vulnerable people with eating disorders or others.